Analisis Teknis dan Ekonomis Penerapan PLTS Pada Perumahan Karyawan Divisi 1 PT. CVA - Nurdiana, Nita; Febrianti, Irine Kartika; Kurniawan, Ian; Rahman, Dui Yanto; Atari, Dadang (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This planning analysis of a solar power generation system (PLTS) as an alternative energy source for longhouse 1, with a total power of 3,180 VA. Based on a daily energy consumption of approximately 38.16 kWh, the calculation of solar panel capacity indicates a requirement of around 48 panels with a capacity of 250 Wp each. The energy storage system is planned using 20 units of 200 Ah, 12 V batteries, with a 5 kWh inverter capacity. The estimated investment cost for the PLTS system is Rp 182,900,000, while the annual operational cost is zero. In comparison, the use of a 3,200 VA generator set (generator diesel) results in an annual cost of Rp 166,800,000. Considering cost and sustainability aspects, PLTS shows long-term advantages despite requiring a higher initial investment. Recommendations are provided for a comprehensive evaluation of energy needs and financial capacity before implementation decisions are made.